Comparison of the second-line treatments for patients with small cell lung cancer sensitive to previous platinum-based chemotherapy: A systematic review and Bayesian network analysis - Shi, Hekai; Guo, Nuojin; Zhao, Zeming; Liu, Ligang; Ni, Tianyi; Zhang, Jinye; Lu, Yingjie (Frontiers in Oncology, 2023)
Objective It remains unclear what the best second-line treatment is for patients with small-cell lung cancer sensitive to previous platinum-based chemotherapy. Methods We systematically screened randomized controlled trials from several online databases. The primary outcome was objective response rate (ORR), and the secondary outcomes were disease control rate (DCR), overall survival (OS), progression-free survival (PFS), and hematological complications graded 3 to 5. The efficacy of included treatments was ranked by surface under the cumulative ranking curve (SUCRA) value. Results We included eleven trials involving 1560 patients in quantitative analysis. Triple chemotherapy containing platinum (TP, combination of cisplatin, etoposide, and irinotecan) was associated with favorable ORR (intravenous topotecan vs TP; odds ratio: 0.13, 95% CI:0.03-0.63; SUCRA, 0.94) and PFS (vs intravenous topotecan; hazard ratio, 0.5; 95% CI: 0.25-0.99; SUCRA, 0.90). Belotecan ranked highest for OS (SUCRA, 0.90), while intravenous topotecan plus Ziv-aflibercept ranked highest for DCR (SUCRA, 0.75). TP was more likely to cause anemia and thrombocytopenia while intravenous topotecan plus Ziv-aflibercept resulted in most neutrocytopenia. Conclusion TP is the first recommendation for the second-line treatment of sensitive relapsed SCLC. TP achieved priority in ORR and PFS with the most frequent adverse effects in anemia and thrombocytopenia. For patients who cannot tolerate the hematological adverse effects of triple chemotherapy, amrubicin is an optional option. Amrubicin had relatively good ORR and PFS, accompanied by fewer hematological complications. The rechallenge of the platinum doublet is inferior to amrubicin in ORR, DCR, and PFS. Oral topotecan has a similar effect compared with IV topotecan, but oral topotecan was associated with slightly higher safety and less stress in nursing. Belotecan contributed to the best PFS with slightly better safety but was not ideal in other outcomes. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022358256.